2008
DOI: 10.1007/s11881-008-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of visual and auditory temporal processing for Chinese children with developmental dyslexia

Abstract: This study examined temporal processing in relation to Chinese reading acquisition and impairment. The performances of 26 Chinese primary school children with developmental dyslexia on tasks of visual and auditory temporal order judgement, rapid naming, visual-orthographic knowledge, morphological, and phonological awareness were compared with those of 26 reading level ability controls (RL) and 26 chronological age controls (CA). Dyslexic children performed worse than the CA group but similar to the RL group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
105
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 70 publications
13
105
1
6
Order By: Relevance
“…In accord with the literature, we found that dyslexic readers required longer ISIs in order to reproduce the order of the tones presented (Ben-Artzi et al, 2005;Chung et al, 2008;Reed, 1980;Tallal, 1989;Tallal & Piercy, 1973a, 1973b. Others have also found poor performance among dyslexic readers on frequency discrimination tasks (Ahissar et al, 2000;Boets, Wouters, van Wieringen, & Ghesquière, 2006;Cacace et al, 2000;Kujala et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In accord with the literature, we found that dyslexic readers required longer ISIs in order to reproduce the order of the tones presented (Ben-Artzi et al, 2005;Chung et al, 2008;Reed, 1980;Tallal, 1989;Tallal & Piercy, 1973a, 1973b. Others have also found poor performance among dyslexic readers on frequency discrimination tasks (Ahissar et al, 2000;Boets, Wouters, van Wieringen, & Ghesquière, 2006;Cacace et al, 2000;Kujala et al, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…These results complement a number of earlier findings which reported that adult dyslexics required longer ISIs to reproduce the order of two tones and longer silent periods within a tone to detect the presence of a gap, relative to the normal reader (Ben-Artzi et al, 2005;Chung et al, 2008;Schaffler, Sonntag, Hartnegg, & Fischer, 2004;Tallal, 1980;Tallal & Piercy, 1973a, 1973bReed, 1989;Van Ingelghem et al, 2001), and confirm the hypothesis that the main difficulty among dyslexic readers is in the processing of temporal-related auditory stimuli. These results suggest that dyslexic readers exhibit a specific deficit in auditory temporal processing and not a general perceptual deficit in auditory processing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, Chinese children with dyslexia seemed to be as good as typical control children at frequency discrimination, but had significantly poorer lexical tone awareness. Chung et al (2008) also explored the associations between temporal order judgment tasks involving rapidly presented visual or auditory stimuli and Chinese reading abilities. They administered tasks of visual and auditory temporal order judgement to 26 children with developmental dyslexia, 26 reading level controls and 26 age-matched controls, along with measures of reading, rapid naming, and phonological awareness.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review of the related literature by Farmer and Klein (1995) has led to the hypothesis that developmental dyslexia is strongly linked to a general deficit in speed of processing (SOP) in both visual and auditory modalities. Chinese children with reading disorders have also been found to show poorer performance than chronological age matched (CA) children with normal reading abilities on visual and auditory temporal processing tasks, and a correlation between reading performance and orthographic processing (Cheung et al, 2009;Chung et al, 2008;Ho & Bryant, 1997;Ho, Chan, Lee, Tsang, & Luan, 2004;Liu, Shu, & Yang, 2009;Siok & Fletcher, 2001). Furthermore, it has been argued that morphological awareness is critical to reading development since Chinese characters represent morphemes, and poor morphological awareness is a core deficit underlying developmental dyslexia in Chinese (Wu, Packard, & Shu, 2009 for review).…”
Section: Introductionmentioning
confidence: 99%